Interpersonal Communication Between Teachers and Parents in Experience-Based Education at Elementary School - Dessy ANDAMISARI; Mirza RONDA; Mikael DUA (International Journal of Environmental, Sustainability, and Social Science, 2024)
Interpersonal communication between teachers and parents in experience-based education at the elementary school level faces challenges such as a lack of openness, empathy, and shared understanding, which can hinder effective learning. This study aims to analyze the interpersonal communication between teachers and parents in experience-based education, identify barriers, and develop effective interpersonal communication strategies. The study is grounded in DeVito’s Interpersonal Communication Theory (openness, empathy, support, positive attitude, equality), Carl Rogers’ Humanistic Theory (authenticity, unconditional acceptance), and John Dewey’s Experience-Based Learning approach. This research employs a qualitative method with a postpositivist paradigm. Data were collected through in-depth interviews, observations, and document analysis, then analyzed using a thematic approach. The findings indicate that openness, empathy, supportive attitudes, positive attitudes, equality, authenticity, and unconditional acceptance in interpersonal communication play a crucial role in enhancing parental involvement in experience-based education. Teachers use various communication strategies, including face-to-face interactions and digital media such as WhatsApp, to foster more inclusive communication. However, major barriers identified include limited direct interaction, differences in expectations between teachers and parents, and technological access constraints affecting communication effectiveness. The novelty of this study lies in the development of interpersonal communication strategies that integrate humanistic and experiential approaches in teacher-parent interactions. Unlike previous studies that primarily focused on teachers' communication within the classroom, this study addresses the gap by proposing an interpersonal communication model based on authenticity and unconditional acceptance, which can enhance parental engagement in experience-based education at the elementary school level.